HPLC Analytical Method Development and Validation Studies of Ondansetron and Rabeprazole. - Udaya Krishna T, Jitendra K, Putta Rajesh Kumar*, Salahuddin Md, Shanta Kumar S.M. (Journal of Biomedical and Pharmaceutical Research, 2012)
Objective: Present investigation involves development and validation of chromatographic method for ondansetron and rabeprazole estimation by HPLC.Methods: The present work describes a validated reverse phase high performance liquid chromatographic method for simultaneous estimation of Rabeprazole and Ondansetron in bulk and pharmaceutical dosage form. Chromatography was performed on a XTerra RP column C18 (150 mm x 4.6 mm i.d., 5 μm) column with mobile phase containing Buffer (phosphate buffer pH 5.5): Water: Methanol (30: 10: 60 v/v/v). The flow rate was 0.6 ml/min and the eluent was monitored at 274 nm. Rabeprazole and Ondansetron were studied for their estimation by RP-HPLC method development and the method was also studied for validation parameters.Results: The selected chromatographic conditions were found to effectively separate Rabeprazole (RT-5.919 min) and Ondansetron (RT- 4.382 min). Linearity for Rabeprazole and Ondansetron were found in the range of 20-100 μg/ml. The values obtained of LODs were 3.06 and 0.06 μg/ml; LOQs were 9.90 and 0.21 μg/ml for Rabeprazole and Ondansetron, respectively. The proposed method was found to be fast, accurate, precise, reproducible and rugged and can be used for simultaneous analysis of Rabeprazole and Ondansetron in combined pharmaceutical formulations. Conclusion: Developed HPLC method was conveniently used for the estimation of ondansetron and rabeprazole in bulk and formulations and the results obtained in this study were uniform, sensitive and reproducible within the limits. Therefore the method is suitable for its intended use for routine analysis of both drug candidates. KEYWORDS: Rabeprazole, Ondansetron, Reversed-Phase HPLC.